Pension systems, intergenerational risk sharing and inflation - Beetsma, Roel M. W. J.; Bovenberg, A.L.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
Everywhere in the industrialized world, population aging is putting social security systems under financial strain. As a result, social security systems are being reformed in many countries. In particular, various countries move from pure pay-as-you-go (PAYG) systems to pension systems that include a larger funded component. At the same time, definedbenefit systems in which benefits are guaranteed by public or corporate sponsors are being replaced by defined-contribution systems in which benefits are subject to various risks.
Economic Papers